Degree of burnout and leadership efficacy among nurse managers in a tertiary maternity hospital in Qatar: A sequential explanatory mixed-methods study - Tapawan, Ana Mari Karla; Silang, John Paul Ben Tabar; Vallesteros, Liwayway T.; Jesus, David Hali de; Fabros, Marietta; Rosa, Ronnell Dela; Tomy, Jim; Ibrahem, Rana Aatif Salim; Al-Lenjawi, Badriya (Belitung Nursing Journal, 2026)
Background: Nurse managers play a critical role in maintaining effective clinical operations and staff performance. However, research examining burnout and leadership efficacy in maternity care settings remains limited. Objective: To examine burnout and leadership efficacy among nurse managers. Methods: A sequential explanatory mixed-methods study was conducted at a tertiary maternity hospital in Doha, Qatar. In Phase I, 125 nurse managers were recruited through convenience sampling and completed the Maslach Burnout Inventory–Human Services Survey for Medical Personnel and the Leadership Efficacy Questionnaire. In Phase II, eight participants were purposively selected for in-depth interviews. Quantitative and qualitative findings were integrated using a joint display approach. Results: Participants reported moderate emotional exhaustion (M = 22.85, SD = 12.69) and depersonalization (M = 7.40, SD = 5.31), alongside high personal accomplishment (M = 42.19, SD = 5.75). Leadership efficacy scores indicated moderate confidence across leader action, leader means, and self-regulation domains. Emotional exhaustion and depersonalization were negatively correlated with all domains of leadership efficacy, whereas personal accomplishment was positively correlated with them. Qualitative findings identified workload, staff management demands, and personal stressors as key contributors to burnout, while resilience, support systems, and adaptive coping strategies were associated with leadership efficacy. Integration indicated that burnout and leadership efficacy co-occur, with inverse associations suggesting that higher burnout is associated with lower leadership confidence, despite sustained functional performance. Conclusion: Burnout and leadership efficacy are significantly associated among nurse managers. Although leadership functioning appears to be maintained, emotional strain is related to reduced leadership confidence. Organizational strategies that address workload demands, strengthen support systems, and promote resilience may help mitigate burnout and support leadership effectiveness.